Aerodynamic performance of a flyable flapping wing rotor with passive pitching angle variation - Chen, Si; Wang, Le; He, Yuanyuan; Tong, Mingbo; Pan, Yingjun; Ji, Bing; Guo, Shijun (Institute of Electrical and Electronics Engineers (IEEE), 2021)
The present work was based on an experimental study on the aerodynamic performance of a flapping wing rotor (FWR) and enhancement by passive pitching angle variation (PPAV) associated with powered flapping motion. The PPAV (in this study 10o~50o) was realized by a specially designed sleeve-pin unit as part of a U-shape flapping mechanism. Through experiment and analysis, it was found that the average lift produced by an FWR of PPAV was >100% higher than the baseline model, the same FWR of a constant pitching angle 30o under the same input power. It was also noted that the lift-voltage relationship for the FWR of PPAV was almost linear and the aerodynamic efficiency was also over 100% higher than the baseline FWR when the input voltage was under 6V. The aerodynamic lift or efficiency of the FWR of PPAV can be also increased significantly by reducing the weight of the wings. An FWR model was fabricated and achieved vertical take-off and free flight powered by 9V input voltage. The mechanism of PPAV function provides a feasible solution for aerodynamic improvement of a bio-inspired FWR and potential application to micro-air-vehicles (MAVs).
Keywords: Flapping wing rotor (FWR); passive pitching angle variation (PPAV); aerodynamic performance; MAVs